Empowering recovery: A case study on conservative management of scapular dyskinesia / Noor Izzati Azhar, Syamil Hazwan Mohd Zaidin and Nur Ainah Mohd Shipah - Azhar, Noor Izzati; Mohd Zaidin, Syamil Hazwan; Mohd Shipah, Nur Ainah (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Scapular dyskinesia, often overlooked in athletes, significantly affects shoulder function and performance. This case study focused on a 23-year-old male badminton player who experienced moderate shoulder pain and limited range of motion after a traumatic injury during a game. The objective was to alleviate pain and improve scapular function through physical therapy approaches. Scapular joint mobilization and strengthening exercises were administered, resulting in reduced pain and increased shoulder joint range of motion. The study demonstrated that conservative management of the scapular joint and muscles had a beneficial effect on athletes with shoulder pain. Addressing scapular issues is crucial to enhance overall shoulder function and support athletes' performance. This research highlights the importance of recognizing scapular dyskinesia as a significant contributor to shoulder pain and advocates for holistic management strategies to aid athletes in their recovery.